The Study of Relationship between Socioeconomic Status and Safety Behaviors in Workers of Subway Construction Project in Qom, Iran - Mohammad Abri; Shahram Vosoughi; Jamileh Abolghasemi; Hajar Taslimi; Hossein Ebrahimi (Muhandisī-i bihdāsht-i ḥirfah/ī, 2022)
Background and Objective: Biological needs are basic human needs for survival according to Maslow's hierarchy of needs. Therefore, the relationship between socioeconomic status and safety behaviors is not far-fetched. The present study aimed to investigate the effect of socioeconomic status on safety behavior in workers of the subway construction project in Qom, Iran. Materials and Methods: The present cross-sectional study was conducted on workers of the subway construction project in Qom in 2020. The sample size was determined by a census of 200 people based on the study criteria. Socioeconomic status and safety behavior questionnaires were subsequently completed for the participants. The data were extracted and analyzed by SPSS software (version 21) after completing the questionnaires. Results: The results of the study revealed no significant relationship between the level of education and safety behavior (P-value> 0.05); however, a significant relationship was observed between that and safety compliance (P-value= 0.006). No significant relationship was discovered between the type of employment and socioeconomic status (P-value=0.008). Also, No significant relationship was found between economic status with safety observation, participation, and behavior (P-value> 0.05). Conclusion: The results of the present study indicated no significant relationship between socio-economic status and compliance, participation, and safety behavior of individuals. Organizational, cultural, and individual factors affect safety and safety behavior along with socioeconomic status. No relationship was observed between socioeconomic status and employee safety behavior which can be attributed to coverage of other factors that failed to be examined in this study.